Effect of Novel Polymer-Free Nitrogen-Doped Titanium Dioxide Film–Coated Coronary Stent Loaded With Mycophenolic Acid - Shim, Jae Won; Kim, Sung Soo; Kim, Hyun Kuk; Bae, In Ho; Park, Dae Sung; Park, Jun-Kyu; Kim, Jae Un; Kim, Han Byul; Lee, Min Young; Kim, Joong Sun; Kim, Jung Ha; Koo, Bon-Sang; et al. (Frontiers in Bioengineering and Biotechnology, 2021)
Background: Titanium is commonly used in blood-exposed medical devices because it has superior blood compatibility. Mycophenolic acid inhibits the proliferation of vascular smooth muscle cells. This study examined the effect of a non-polymer TiO2 thin film–coated stent with mycophenolic acid in a porcine coronary overstretch restenosis model. Methods: Thirty coronary arteries in 15 pigs were randomized into three groups in which the coronary arteries were treated with a TiO2 film–coated stent with mycophenolic acid (NTM, n = 10), everolimus-eluting stent with biodegradable polymer (EES, n = 10), or TiO2 film–coated stent (NT, n = 10). A histopathologic analysis was performed 28 days after the stenting. Results: There were no significant intergroup differences in injury score, internal elastic lamina area, or inflammation score. Percent area stenosis was significantly smaller in the NTM and EES groups than in the NT group (36.1 ± 13.63% vs. 31.6 ± 7.74% vs. 45.5 ± 18.96%, respectively, p = 0.0003). Fibrin score was greater in the EES group than in the NTM and NT groups (2.0 [range, 2.0–2.0] vs. 1.0 [range, 1.0–1.75] vs. 1.0 [range, 1.0–1.0], respectively, p < 0.0001). The in-stent occlusion rate measured by micro-computed tomography demonstrated similar percent area stenosis rates on histology analysis (36.1 ± 15.10% in NTM vs. 31.6 ± 8.89% in EES vs. 45.5 ± 17.26% in NT, p < 0.05). Conclusions: The NTM more effectively reduced neointima proliferation than the NT. Moreover, the inhibitory effect of NTM on smooth muscle cell proliferation was not inferior to that of the polymer-based EES with lower fibrin deposition in this porcine coronary restenosis model.